Practical realisation of a return map immune Lorenz‐based chaotic stream cipher in circuitry. Issue 6 (1st October 2018) - Brown, Daniel; Hedayatipour, Ava; Majumder, Md. Badruddoja; Rose, Garrett S.; McFarlane, Nicole; Materassi, Donatello
Abstract : The authors report on the realisation of an encryption process in real‐time analogue circuitry using on‐the‐shelf components and minimal processing power. Self‐synchronisation of two similar systems through a single shared state is a unique property of the chaotic Lorenz attractor system. In this process, the single parameters of the system are modulated to mask a message before transmitting securely through a single‐shared state. However, these techniques are vulnerable to the return map attack. They show that time‐scaling can further obfuscate the modulation process and improve return map attack immunity and demonstrate a fabricated printed circuit board implementation of the system.